The relationship between genome size, morphological parameters and diet breadth in insect species. (July 2019) - Gandhi Gracy, R.; Basavaarya, B.R.; Kariyanna, B.; Arunkumara, C.G.; Jalali, S.K.; Venkatesan, T.; Ballal, Chandish R.; Mohan, M.
Abstract: Genome size estimation is the first step involved in the complete genome sequencing project. Knowledge on genome size is also useful in research work related to genetics, molecular biology, and systematics. Though there are many methods of genome estimation, the Propidium Iodide (PI) based flow cytometry is simple and gives an accurate estimation. In the present investigation, the diploid genome size of four insect species viz., cotton leafhopper, Amrasca biguttula biguttula (392.47 Mb) (Cicadellidae: Hemiptera), bean pod borer, Maruca vitrata (1489.63 Mb) (Crambidae: Lepidoptera), tomato pinworm, Tuta absoluta (1128.61 Mb) (Gelechiidae: Lepidoptera) and eggplant shoot and fruit borer, Leucinodes orbonalis (944.52 Mb) (Crambidae: Lepidoptera) were estimated using chicken RBC (2.33 pg) as a reference standard. The relationship of genome size with the insect morphological traits and host plant range showed no evident correlation between them.